1999
DOI: 10.1029/1999jd900293
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year continuous record of nitrogen trace gas fluxes from untreated and limed soil of a N‐saturated spruce and beech forest ecosystem in Germany: 1. N2O emissions

Abstract: Abstract. For 3 years we followed the complete annual cycles of N20 emission rates with 2-hour resolution in spruce and beech plantations of the H6glwald Forest, Bavaria, Germany, in order to gain detailed information about seasonal and interannual variations of N20 emissions. In addition, microbiological process studies were performed for identification of differences in N turnover rates in the soil of a spruce and a beech site and for estimation of the contribution of nitrification and denitrification to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
189
5
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(230 citation statements)
references
References 55 publications
35
189
5
1
Order By: Relevance
“…However, most of these estimates were obtained from small experimental field plots, which may not be representative of production-scale fields. Therefore, most currently used simulation models fail to account for large pulses of N 2 O emissions caused by spring thawing (130), rapid soil warming (131), tillage and irrigation events (132), and N application (120), which may greatly affect annual emission rates and the net global warming potential of an agroecosystem (133). And although C sequestration is often increased in systems that receive N fertilizer, the energy costs of N fertilizer and associated CO 2 emissions must also be included in the net greenhouse forcing budget (134).…”
Section: Soil Quality Nitrogen Requirements and Greenhouse Gas Emismentioning
confidence: 99%
“…However, most of these estimates were obtained from small experimental field plots, which may not be representative of production-scale fields. Therefore, most currently used simulation models fail to account for large pulses of N 2 O emissions caused by spring thawing (130), rapid soil warming (131), tillage and irrigation events (132), and N application (120), which may greatly affect annual emission rates and the net global warming potential of an agroecosystem (133). And although C sequestration is often increased in systems that receive N fertilizer, the energy costs of N fertilizer and associated CO 2 emissions must also be included in the net greenhouse forcing budget (134).…”
Section: Soil Quality Nitrogen Requirements and Greenhouse Gas Emismentioning
confidence: 99%
“…Several independent studies have demonstrated that N 2 O is emitted in significant quantities from forest ecosystems (e.g. Ambus and Christensen, 1995;Bowden et al, 1990;Schmidt et al, 1989;Struwe and Kjøller, 1994;Papen and Butterbach-Bahl, 1999). In Europe, forest ecosystems cover about 1.9 Mill.…”
Section: Introductionmentioning
confidence: 99%
“…Although abiological processes (e.g., chemodenitrification) may account for a small portion of total soil derived N 2 O, the biological processes of nitrification NH are believed to be the predominant sources of N 2 O production in soils (Williams et al 1992;Wrage et al 2001). Forest soils have been acknowledged to represent significant sources of N 2 O emission (Papen and Butterbach-Bahl 1999;Butterbach-Bahl et al 2002;Skiba et al 2004). The dominant source for N 2 O from tropical forest soils was estimated to be in the range of 2.2-3.7 Tg N year −1 (24% of the total source strength) to the global atmospheric N 2 O budget (Prather and Ehhalt 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Soil biological N 2 O production is controlled by a set of physical, chemical and biological factors. Soil moisture content, soil temperature and nutrient availability are regarded as key in regulating soil N 2 O production in forests (Papen and Butterbach-Bahl 1999;Brumme et al 1999;Smith et al 2003). An increase in these factors usually enhances N 2 O emission from forest soil.…”
Section: Introductionmentioning
confidence: 99%